(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The study discussed the reports and the standards prepared by the companies that have shares in the financial markets, specifically Khartoum Financial Markets which lacks the satisfactory information that enable the shareholders to take decisions for investment and securities. The statements on the screen are the major source to provide the appropriate information because they should include the required accounting standards as reliable resources for decision taking and should be stable and easily applied at any time. The impact of standards that arrange the accounting policy is the pillar that holds the financial statements which are considered the basic principle of providing the accounting information used for decision taking about the investment and determining the actual value of shares in the financial markets based on correct scientific statements. Thus, the participating companies would grasp the opportunity to change their accounting policies of the standards and the accounting evaluation on the appropriate time. The Objectives: - To know the determining facts the activate the accounting information used in taking decision on shares investment and the consequences. - To endeavor to improve the quality of the accounting information prior to decision taking and all that should trust and abide the international standards. - To issue the reasonable proposals to facilities the best application for the disclosure tools accounting to the international accounting standards. The researcher followed asset of research procedures, such as the deduction approach in determining the problem and setting the hypothesis, the extrapolation approach for following the problem, the historical method I the humanitarian studies. And the analytical descriptive method for testing the hypothesis. Then the Study Tested the Validity of the Following Suppositions: - Due to the absence of accounting standards, the participating companies will control the quantity and quality of the information to dominate the market. - The arrangement of the accounting policies won’t be achieved unless there them are accounting and auditing standards with strict abidance to apply. - The registered companies in Khartoum financial market dared not to send regular financial reports and that obliged the shareholder to gather his own information. - The availability of accounting standards at the financial market satisfy the needs of shareholders and that will benefit the market and encourage it to practice wide investment. Moreover, the conformity to the discloser standards by the registered companies in Khartoum financial market increases the trust of companies on the financial statements. Eventually, the companies will rely on these statements when they want to take decisions of investment. The Results: - The absence of the accounting standards is almost prevailing because most of the companies do not abide the application of the accounting standards to arrange their accounting policies. - The participating companies in Khartoum financial market do not conform to apply the accounting standards approved by Khartoum financial market, and consequently they will have the control on the declared quality and quality of financial information. - The Council of Legal Accountants lacks the sufficient support to issue accounting standards. - The refraining of companies to present reports on the future financial information makes it impossible to foretell investment decision taking. Recommendations: - To strengthen information to improve awareness of investment. - To issue the rules of share to organize and raise the efficient economic performance and support the awareness of investment. - To conform the registered companies in Khartoum financial market to elaborate the disclosure in the reports and statements in conformity to the international accounting standards.